Історико-правові аспекти основ правового статусу суддів у період Київської Русі, Галицько-Волинської та Литовсько-Руської держави (ІХ ст. – середина ХVI ст.) - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проведено історичний аналіз генезису правового статусу суддів в період Київської Русі, Галицько-Волинської та Литовсько-Руської держави. Відзначається, що в цей ранній період починають встановлюватись окремі елементи правового статусу суддів, зокрема: вимоги, які пред’являються до суддів; порядок їх обрання та призначення; присяга суддів; повноваження суддів; відповідальність суддів; гарантії безпеки для суддів. Інститут суддів відігравав різну роль та мав специфічний політико-правовий статус у залежності від етапів розвитку феодального суспільства тих часів.The article offers historical analysis of the genesis of the judge’s legal status in the period of Kievan Rus, Galicia-Volyn and Lithuanian-Rus state which were characterized by caste division of society, feudal relationships system and practically unlimited power of the Prince in all spheres of social life, including legal proceedings. The emphasis is laid on the institute of legal status of judges, which was confirmed and developing, although it played different roles in each particular case and had a special political and legal status, depending on the stage of the feudal society development in that time. It is noted that in that early period some elements of the legal status of judges started to be established, including: the requirements that can be applied to judges; procedure of their election and appointment; oath of judges; powers of judges; responsibility of judges; security guarantees for judges. During the period of XIVth - first half of XVIth century the status of the judges was a secondary status after that of the state official. In the domenian courts judge’s functions were performed by landlords (in the domenian church – by spiritual lords) or by the appointed by them officials, regardless their legal literacy. There were no special professional requirements to the judges of state courts.
Historical and Legal Aspects of the Legal Status of Judges in the Period of the Kievan Rus, Galicia-Volyn and Lithuanian-Rus State (the XIV-th century - the middle of the XVI-th century)
Keywords: правовий статус; правовий статус судді; правосуддя; суддя; судова система; legal status; legal status of judges; justice; judge; judicial system